Dancing with Uncertainty: Unraveling Firm Investment Inefficiencies in the Asia Pacific Region - Rita Juliana; Liza Handoko; Nicholas Lee (Journal of Economics, Business, and Accountancy Ventura, 2024)
This study explores the intricate relationship between uncertainty and corporate investment inefficiencies in the Asia-Pacific region, utilizing data from non-financial firms between 2008 and 2021. The method used in the study is fixed effect regression with Driscoll-Kraay robust standard error. The empirical analysis unveils that uncertainty leads to overinvestment. This phenomenon is more pronounced in middle and low-income economies, while high-income countries display a distinct trend of less susceptibility to uncertainty-induced suboptimal investment choices. The study’s implications extend to policymakers and industry stakeholders, urging a closer examination of firms’ risk management strategies, particularly considering the strategic potential of overinvestment as a buffer against uncertainty’s adverse effects. This holds particular significance in the dynamic economic landscape of the Asia-Pacific countries, where the study contributes to a deeper understanding of the interplay between uncertainty and inefficiency of investment decisions across diverse economic settings.